SISTEM INFORMASI AKUNTANSI PENJUALAN PADA PT. XYZ - Hnarti, inna; Nabila Zhafirah Haryono; Suhardianto (ASIAN PUBLISHER, 2024)
This study aims to determine the related parts, documents used and flowcharts in the Sales Accounting Information System at PT. XYZ. The Accounting Information System is a subsystem of the management information system that provides accounting and financial information as well as other information obtained from the routine processing of accounting transactions at PT. XYZ. The method used in this study is a qualitative descriptive method with data collection techniques through interviews, observations, and documentation. Based on the results of the research conducted, it shows that the related parts in the Sales Accounting Information System at PT. XYZ have functioned well according to their respective roles and responsibilities. The documents used in the Sales Accounting Information System at PT. XYZ have been systematically structured and meet the needs of the sales process, and the flowchart in the Sales Accounting Information System at PT. XYZ has been designed with a clear and comprehensive structure